Therapeutic and Safety Evaluation of Combined Aqueous Extracts of Azadirachta indica and Khaya senegalensis in Chickens Experimentally Infected with Eimeria Oocysts - J. G. Gotep; J. T. Tanko; G. E. Forcados; I. A. Muraina; N. Ozele; B. B. Dogonyaro; O. O. Oladipo; M. S. Makoshi; O. B. Akanbi; H. Kinjir; A. L. Samuel; T. E. Onyiche; et al. (Journal of Parasitology Research)
Coccidiosis is a disease of economic importance in poultry causing morbidity and mortality. Reports show that Azadirachta indica and Khaya senegalensis have been used individually in the treatment of avian coccidiosis. We thus investigated the efficacy and safety of the combined aqueous extracts of these plants for the treatment of experimentally induced coccidiosis in broiler chickens using oocyst count, oxidative stress biomarkers, serum biochemistry, histology, and haematological parameters. The phytochemical screening revealed the presence of tannins, saponins, cardiac glycosides, and steroids in both extracts. In addition, alkaloids and flavonoids were present in Azadirachta indica. There was significant (p<0.05) dose dependent decrease in oocyst count across the treatment groups with 400 mg/kg of the combined extract being the most efficacious dose. Immunomodulatory and erythropoietic activity was observed. There were decreased intestinal lesions and enhanced antioxidant activity across the treatment groups compared to the negative control. Administration of the combined extract did not cause damage to the liver as ALT, AST, and ALP levels were significantly reduced in the uninfected chickens treated with the extracts compared to control suggesting safety at the doses used. The combined aqueous extracts of K. senegalensis stem bark and Azadirachta indica leaves were ameliorative in chickens infected with coccidiosis.